Employment of exploratory factor analysis to extract factors Organizational Loyalty and job satisfaction Case Study in the College of Technology Management – Baghdad - نامق, فيصل ناجي (Journal of Economics and Administrative Sciences, 2013)
According to the measuring the relationship between organizational loyalty and job satisfaction among staff members at one college in the higher education ministry in Iraq by using exploratory factor analysis methods to extraction the components which have the major effects on the variables related to organizational loyalty and job satisfaction .The research contains four basic topics، the first section related to methodology and regarding the conceptual framework it is discussed in the second section، and the third section concentrated at the presentation and the analysis Scientific results and practical results are section presented in the fourth.